The Hubungan Lama Pemakaian Suntik DMPA dengan Penurunan Libido pada Akseptor Suntik DMPA di Praktik Mandiri Bidan Hana Sri Wuryaningsih Parakan - Hana Sri Wuryaningsih; Dian Monalisa Rusliani; Riska Ismawati Hakim (Journal of Health (JOH))
Long-term use of DMPA injectable contraceptives can lower estrogen levels, affect hormone metabolism, and lower serum estradiol levels, resulting in decreased female sexual function. Injectable DMPA birth control shows significant sexual dysfunction effects if used for more than 2 years. The purpose of this study was to determine the relationship between prolonged use and decreased libido in DMPA injectable birth control acceptors at PMB Hana Sri Wuryaningsih.  The research design uses descriptive correlative with a cross sectional approach. The population in this study was all DMPA injectable KB acceptors at PMB Hana Sri Wuryaningsih as many as 141 people. The sampling technique uses Purposive sampling. The number of samples was 104 respondents. This research instrument used questionnaires. Univariate analysis with frequency distribution table and bivariate analysis with Chi Square test.